Immune status of children with and without severe infection during remission of malignant disease. Issue 5969 (31st May 1975) - Graham-Pole, J; Willoughby, M L; Aitken, S; Ferguson, A
Abstract : The immune status of children with malignant disease in remission was assessed usingvarious immune function tests. Children with infections had significantlymore neutropenia, hypogammaglobulinaemia, and impaired cell-mediated immune responses than those without. These two groups combined had much more absolute lymphopenia and impairment of both cell-mediated immunity and antibody-producing capacity thancontrol children with non-malignant conditions. Regular immunological evaluation isrecommended for children with malignant disease when new intensive treatment schedules are under trial and for individual patients particularly prone to develop infections during treatment.